Congenital dilatation of the intrahepatic bile ducts associated with the development of amyloidosis. Issue 8 (August 1972) - Fevery, J.; Tanghe, W.; Kerremans, R.; Desmet, V.; De Groote, J.
Abstract : Two cases of pure congenital dilatation of the intrahepatic bile ducts are presented. One patient developed amyloidosis secondary to suppuration, and had isolated cysts in the renal medulla. The position of congenital dilatation of the intrahepatic bile ducts compared with cysts in the liver and its association with `cystic' diseases of the kidneys is discussed.